Effects of Alpinia Officinarum and Euodia Rutaecarpa on the expression of TRPA1 and TRPM8 in rats with irritable bowel syndrome - Jiahui HE; Yuying ZHANG; Chaoyan YANG; Kunping LI; Xujiang YUAN; Zihong ZHANG; Chiming GU; Yanfen CHEN (KeAi Communications Co., Ltd., 2023)
Objective: Alpinia Officinarum and Euodia Rutaecarpap are two traditional Chinese herbs with warm nature, usually called interior-warming medicinal and widely used to treat cold syndrome for a long history. The purpose of this study is to explore the effects of Alpinia Officinarum and Euodia Rutaecarpap on irritable bowel syndrome (IBS) rats with spleen-stomach deficiency cold syndrome, and to clarify the link between "warming the middle to alleviate pain" and transient receptor potential channel A1 (TRPA1), M8 (TRPM8). Methods: IBS rat model with spleen-stomach deficiency cold syndrome was established by cold diarrhea and restraint stress. Rats were randomly divided into the normal group, model group, positive group (pinaverium bromide), Alpinia Officinarum group and Euodia Rutaecarpa group. After continuous modeling and administration for seven days, body weight, loose stool grades, activity of ATP enzyme, pathological morphology of gastrointestinal tissue were evaluated. The expression of TRPA1 and TRPM8 in spinal ganglion, stomach and colon tissue of rats were detected by RT-PCR and immunohistochemistry. Results: The IBS model with spleen-stomach deficiency cold syndrome caused increase in the number of diarrhea and loss in the body weight in rats. Compared with the normal group, the loose stool grades of model group was significantly increased (P<0.01), Na+-K+-ATP and Ca2+-Mg2+-ATP activity of erythrocyte membrane were significantly decreased (P<0.01). However, compared with the model group, Alpinia Officinarum and Euodia Rutaecarpa obviously reduced the loose stool grades (P<0.05 or P<0.01), and obviously increased the activity of Na+-K+-ATP and Ca2+-Mg2+-ATP (P<0.05). The expression of TRPA1 and TRPM8 in spinal ganglia and colon tissue of the model group was markedly enhanced (P<0.01), but Alpinia Officinarum and Euodia Rutaecarpa significantly inhibited these overexpression. Conclusion: The effect of interior-warming and alleviating pain of Alpinia Officinarum and Euodia Rutaecarpa on IBS model may be mainly achieved by regulating the abnormal expression of TRPA1 and TRPM8. Thus, these results could support the fact that interior-warming medicinal such as Alpinia Officinarum and Euodia Rutaecarpa are traditionally used to cure spleen-stomach deficiency cold syndrome.